2003
DOI: 10.1088/0953-8984/15/40/024
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the thermal dissolution process of the Suzuki phase of the Eu2+ion in KBr single crystals by analysis of photoacoustic signals

Abstract: An experimental investigation of the thermal behaviour of the dissolution process of the Suzuki phase (SP) by continuous heating (1 °C min−1) of KBr:Eu2+ crystals is reported in this work. The thermal profiles were determined by the correlation functions between subsequent photoacoustic (PA) signals registered during the dissolution process. The behaviour of the thermal profile is directly related to the absorption coefficient of the Eu2+ ion in precipitated states that are present in the crystal. The PA sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Single crystals of europium-doped KBr were grown by the Czochralski method under a controlled atmosphere of dry argon. The experimental details and photoacoustic signal analysis are similar to those describes in a previous paper [7].…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Single crystals of europium-doped KBr were grown by the Czochralski method under a controlled atmosphere of dry argon. The experimental details and photoacoustic signal analysis are similar to those describes in a previous paper [7].…”
Section: Methodsmentioning
confidence: 91%
“…On the other hand, recent experimental work on the relation between the optical absorption coefficient and precipitated states detected by photoacoustic technique [6] has been carried out and it was shown that these measurements could be used as an alternative technique to investigate precipitation processes of impurity-doped alkali halides [7]. The precipitate size increases with an increase of the impurity concentration and with a decrease in the crystal cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NS starts dissolving at 80 1C and at 120 1C it has disintegrated. In the region labeled X, the last values are zero due to the extinction of the excitation peak, indicating that the NS have been destroyed [28,29]. As a consequence of the thermal dissolution of the NS in SP, the peak wavelength is shifted to 233 nm until the band disappears at 120 1C.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…In general the alkali halide single crystals doped with divalent impurities tend inevitably to form precipitates/aggregates, and depending on the thermal treatment applied, they can form the SP [26,[27][28][29][30], in particular, for NaCl: Mn 2 þ in as-grown samples or samples stored for a long time at room temperature (RT) or around 120 1C. An SP structure consists of a three-dimensional periodic arrangement formed by a divalent cation and its corresponding second nearest monovalent cation vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, also other metal impurity cations such as Mn 2+ [13,14], [16]- [19], [36], [40]- [42], [45]- [50], Mg 2+ [1,21,36,41,42], Fe 2+ [15,17,19,36,41,42,51], Ni 2+ [42,52], Co 2+ [53], Sr 2+ [42,54] and Pb 2+ [42,55] have been the subject of many investigations and discussions. In fact, the host lattice need not necessarily be NaCl: the Suzuki phase may exist also in NaBr (Mn 2+ [50]), KCl (Sm 2+ [57], Pb 2+ [58] and Eu 2+ [56,59]), KBr (Mn 2+ [60] and Eu 2+ [59,61,62]), LiF (Mg 2+ [11,63]) and AgCl (Pb 2+ [64]) and even in oxides (MgO:Mn 4+ [31], [65]- [67], NiO:Mn 4+ [67] and CuO:Pb 4+ [32,68]). Suzuki phases including two types of metal impurity cations have even been studied ...…”
Section: The Suzuki Structurementioning
confidence: 99%